2016
DOI: 10.3390/ijms17081256
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Lipid Accumulation by Indole-3-Carbinol Is Associated with Increased Expression of the Aryl Hydrocarbon Receptor and CYP1B1 Proteins in Adipocytes and with Decreased Adipocyte-Stimulated Endothelial Tube Formation

Abstract: This study investigated the effects of indole-3-carbinol (I3C) on adipogenesis- and angiogenesis-associated factors in mature adipocytes. The cross-talk between mature adipocytes and endothelial cells (ECs) was also explored by cultivating ECs in a conditioned medium (CM) by using I3C-treated adipocytes. The results revealed that I3C significantly inhibited triglyceride accumulation in mature adipocytes in association with significantly increased expression of AhR and CYP1B1 proteins as well as slightly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…This finding appears contradictory to the mechanical stress‐induced CYP1B1 upregulation that was associated with an impaired adipogenic differentiation. However, Wang et al () demonstrated that an indole‐3‐carbinol‐induced decrease in lipid accumulation in 3 T3‐L1 adipocytes correlated with an increased aryl hydrocarbon receptor (AhR) and CYP1B1 expression. CYP1B1 is regulated via AhR activation, which is considered to play a negative role in adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This finding appears contradictory to the mechanical stress‐induced CYP1B1 upregulation that was associated with an impaired adipogenic differentiation. However, Wang et al () demonstrated that an indole‐3‐carbinol‐induced decrease in lipid accumulation in 3 T3‐L1 adipocytes correlated with an increased aryl hydrocarbon receptor (AhR) and CYP1B1 expression. CYP1B1 is regulated via AhR activation, which is considered to play a negative role in adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…84 The AhR agonist indole-3-carbinol decreases lipid accumulation and expression of NRF2, hormone-sensitive lipase (HSL) and GAPDH in mature adipocytes. 85 AhR also affects the lipolysis function of mature adipocytes. Lipolysis functions as an important regulator of systemic energy homeostasis by providing the body with free fatty acids during fasting and exercise.…”
Section: Adipose Tissue and Lipid Metabolismmentioning
confidence: 99%
“…On this point, a novel study in children and adolescents chronically treated with RSP found that iron status was inversely corelated with weight gain, contributing to dysmetabolic iron overload syndrome (DIOS) ( 135 ). This is significant as intracellular iron increases the risk of ROS generation that cannot be counteracted as Bacteroidetes depletion lowered IPA, a key gut antioxidant ( 98 , 136 , 137 ). Restoration of the adequate levels of AhR and PXR ligands via diet, pre, probiotics, or microbial transplant may upregulate Bacteroidetes phylum, attenuating psychotropic drugs-induced weight gain ( 138 ).…”
Section: Psychotropic Drugs As Antimicrobialsmentioning
confidence: 99%